International Financial Reporting Standards Adoption and Earnings Management: The Fundamental Effect Framework - Chizue, NWAUBANI Anthony Nzeribe (Financial Risk and Management Reviews, 2020)
The study mainly examined effect of adoption of International Financial Reporting Standards on earnings management and earnings quality in banks using a new approach - Fundamental Effect Framework. Specifically, effect on profit after tax, net interest income and ratio of loan loss provisioning of the Nigerian banks were examined. Ex-post facto research design was adopted. Secondary data on nine listed deposit money banks were analyzed using Paired Student t-test. The banks were those whose annual financial reports for 2011 and 2012 were available and contained figures under Nigerian GAAP and IFRS-equivalent of the 2011 figures. Findings revealed that IFRS adoption in Nigeria results in insignificant rise in earnings management and low earnings quality as measured by Profit After Tax and Ratio of Loan Loss Provision but leads to insignificant reduced earnings management and improved earnings quality in terms of net interest income. It is concluded that though some individual banks recorded significant reduction in earnings management under IFRS, fundamentally, the adoption in has no significant effect on earnings management and earnings quality of the banks based on the reported performance as at the date of the mandatory adoption in Nigeria. The study recommends inter-alia that IFRS Foundation and the national reporting authorities in all IFRS jurisdictions should monitor implementation and application of IFRS9 to minimize likely manger’s discretion under the “forward -looking expected- credit loss” model of the IFRS 9.